2011
DOI: 10.1016/j.ajpath.2010.11.058
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CXCL5 Is Associated With Poor Survival in Patients With Pancreatic Cancer

Abstract: Epithelial neutrophil-activating peptide-78 (CXCL5), a member of the CXC chemokine family, has been shown to be involved in angiogenesis, tumor growth, and metastasis. The objective of this study was to determine the relationship between CXCL5 expression and tumor progression in human pancreatic cancer and to elucidate the mechanism underlying CXCL5-mediated tumor angiogenesis and cancer growth. We report herein that CXCL5 is overexpressed in human pancreatic cancer compared with paired normal pancreas tissue.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
124
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(132 citation statements)
references
References 41 publications
5
124
2
1
Order By: Relevance
“…These authors also performed xenograft assays in nude mice, in which they used shRNA downregulation of CXCL5 or antibody-mediated neutralization of CXCR2 and showed attenuation of pancreatic tumor cell growth. They also demonstrated that CXCL5 derived angiogenesis development was ERK, AKT and signal transducer and activator of transcription mediated signaling pathways [156] . Moreover, in a clinical study that analyzed 52 PACs and 52 pancreatic neuroendocrine tumors, Hussain et al [157] found that expression of CXCL8 and its receptors CXCR1/2 were significantly upregulated compared to normal pancreatic tissues, a finding confirmed by immunohistochemistry and qRT-PCR.…”
Section: Pancreasmentioning
confidence: 99%
See 2 more Smart Citations
“…These authors also performed xenograft assays in nude mice, in which they used shRNA downregulation of CXCL5 or antibody-mediated neutralization of CXCR2 and showed attenuation of pancreatic tumor cell growth. They also demonstrated that CXCL5 derived angiogenesis development was ERK, AKT and signal transducer and activator of transcription mediated signaling pathways [156] . Moreover, in a clinical study that analyzed 52 PACs and 52 pancreatic neuroendocrine tumors, Hussain et al [157] found that expression of CXCL8 and its receptors CXCR1/2 were significantly upregulated compared to normal pancreatic tissues, a finding confirmed by immunohistochemistry and qRT-PCR.…”
Section: Pancreasmentioning
confidence: 99%
“…Furthermore, another report suggests that CXCL5 may be a possible prognostic biomarker for pancreatic cancer. Li et al [156] reported that overexpression of CXCL5 is correlated with poorer tumor differentiation, advanced clinical stage, and shorter patient survival. These authors also performed xenograft assays in nude mice, in which they used shRNA downregulation of CXCL5 or antibody-mediated neutralization of CXCR2 and showed attenuation of pancreatic tumor cell growth.…”
Section: Pancreasmentioning
confidence: 99%
See 1 more Smart Citation
“…16 CXCL5 binds with CXCR1 and CXCR2 and activates MAP kinase and PI3 kinase signaling pathways. 17 It has been reported that CXCL5 levels are significantly increased in rheumatoid arthritis. 18 Moreover, inflammatory cytokine IL1b has been shown to induce CXCL5 expression by activation of NF-kB and CREB.…”
mentioning
confidence: 99%
“…16 CXCL5 binds with CXCR1 and CXCR2 and activates MAP kinase and PI3 kinase signaling pathways. 17 It has been reported that CXCL5 levels are significantly increased in …”
mentioning
confidence: 99%